Pelatihan Pengelolaan E Commerce Bagi Usaha Produktif Di Nagari Bukik Batabuah, Kabupaten Agam - Yohan Fitriadi; Wellia Novita (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
This training plays a crucial role in providing training to 37 participants in Nagari Bukit Batabuah, Agam Regency. It focuses on micro, small, and medium-sized enterprises (MSMEs) in the region. Pre-training needs analysis helped the community service team understand the challenges faced by the partners and identify their primary needs. Survey data indicates that the majority of participants have been actively involved in various business sectors, with many already owning their businesses. Income analysis suggests income variation, with most participants falling into the middle and upper-middle-income categories. In the context of digital marketing, Shopee emerges as the primary platform chosen by participants, while diversification through WhatsApp Business, Facebook, and Instagram is also evident. This training provides a deep understanding and practical skills to MSME entrepreneurs, assisting them in developing effective marketing strategies and leveraging the full potential of online media for business growth